2020
DOI: 10.1016/j.jiph.2019.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of MERS-CoV spike protein gene in Saudi Arabia

Abstract: a b s t r a c tBackground: Middle East respiratory syndrome coronavirus (MERS-CoV) was primarily detected in 2012 and still causing disease in human and camel. Camel and bats have been identified as a potential source of virus for disease spread to human. Although, significant information related to MERS-CoV disease, spread, infection, epidemiology, clinical features have been published, A little information is available on the sequence diversity of Spike protein gene. The Spike protein gene plays a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
4
12
0
Order By: Relevance
“…In Genetic diversity has been reported in some studies particularly in the spike gene, which has implication of evolving tropism and transmissibility. Such studies reported high genetic variability with other published MERS-CoV sequences, the nucleotide sequence identity ranged from 65.7% to 99.8% (29). However, other studies reported relatively high genetic stability among MERS-CoV isolates, which is consistent with our findings (30,8).…”
Section: Seroprevalence Of Mers-cov In Slaughterhouse Camels In Riyadhsupporting
confidence: 91%
“…In Genetic diversity has been reported in some studies particularly in the spike gene, which has implication of evolving tropism and transmissibility. Such studies reported high genetic variability with other published MERS-CoV sequences, the nucleotide sequence identity ranged from 65.7% to 99.8% (29). However, other studies reported relatively high genetic stability among MERS-CoV isolates, which is consistent with our findings (30,8).…”
Section: Seroprevalence Of Mers-cov In Slaughterhouse Camels In Riyadhsupporting
confidence: 91%
“…191 However, the propensity of CoVs to rapidly mutate and recombine poses a potential problem for vaccine development. [192][193][194] Furthermore, the enhanced disease after viral challenges postvaccination has been observed in animal models after several different vaccines. [195][196][197]…”
Section: Vaccinesmentioning
confidence: 99%
“…We next determined whether analogous changes in S1A of the related MERS-CoV also modified viral attachment. The S1A interaction with sialic acids has biological significance, as antibodies against S1A protect mice from lethal MERS-CoV infections (55), and S1A acquires adaptive mutations in humans (56) and in mouse models of human MERS-CoV lung infection (57,58). In mice, this selectivity was at Asn222 (57, 58), a known glycan addition site (17,59,60), and a documented hypervariable residue, evident in a group of MERS-CoV-related HKU4 bat viruses but absent in the HKU5 bat virus groups (Fig.…”
Section: Mers-cov Spikes Mediate Cell Fusion Without Requiring Hdpp4 mentioning
confidence: 99%